PEMBUATAN APLIKASI KEUANGAN SEDERHANA BERBASIS EXCEL GUNA MEMBANTU PELAPORAN KEUANGAN UMKM AYAM KEFREC & COFFEESHOP SHINE AND SMILE CAR WASH - Muhammad Abdul Karim; Dhining Putri Herianti; Bertilia Lina Kusrina; Ira Phajar Lestari; Melisa Melisa; Nur Asih Paridah (Bisnis Manajemen dan Keuangan, 2024)
This research report aims to: (1) recapitulate the initial balance data for 2022 and 2023, (2) record and input financial data into the excel application. In this study, several methods were used, namely observation, interviews and literature studies. The results obtained while carrying out the research are to make steps for preparing financial statements. In the preparation of financial statements consists of several steps including: (1) recording and identifying data in MSMEs, (2) account codes, (3) opening balances, (4) general journals, (5) ledgers, (6) trial balance, (7) adjusting journal paragraphs, (8) income statements, (9) equity statements, (10) balance sheets, (11) cash flow statements, (12) closing journals, and (13) balance sheets after closing. The preparation of financial statements using the excel application makes the financial statements more effective and efficient